Baby girl with pentalogy of Cantrell: a case report on an extremely rare condition - Widiastuti Soewondo; Suyono Suyono; Johannes Berchmans Prasodjo; Sri Lilijanti Widjaja (Indonesian Pediatric Society, 2019)
In 1958, Cantrell et al. described an extremely rare syndrome of congenital defects involving the abdominal wall, sternum, diaphragm, pericardium, and heart malformation.1 The incidence of pentalogy of Cantrell (POC) is one in 65,000 live births.1,2,3 Only one case was reported in Dr. Moewardi Public Hospital between 1999 and 2016. The exact etiology of this condition is unknown, but developmental failure of mesoderm at 4 weeks of gestational age may contribute to the condition.4 The prognosis depends on the degree of heart failure and the malformations that occur. Heart failure, arrhythmia, cardiac rupture, cardiac tamponade, endocarditis, and peripheral emboli are described as the main complications and causes of death.5,6 The aim of this report was to add to reference data about complete POC and the prognostic outcome.